Motorcycle Helmet Use In Calicut, India: Users Behaviour, Attitude And Perceptions - Krishnamurthy Karuppanagounder AND Arjun V Vijayan (Traffic Injury Prevention, 2015)
Objectives: The objectives of this study include assessing the motorcycle helmet usage pattern in Calicut, India and analysing the factors influencing the helmet usage from the motorcyclists’ perception. Methods: Field observational studies at fifteen locations were conducted to find out the helmet usage rate among motorcyclists and pillion passengers. A structured questionnaire interview survey was conducted with 709 motorcyclists to evaluate the users’ perceptions and opinions in using motorcycle helmets. Results: There was a considerable difference in the level of motorcycle helmet usage observed between the locations within and outside the city limit, where different level of helmet law enforcement was exercised. The helmet usage was observed to a maximum of 89% within the city and to a minimum of 23% in some locations outside the city. The decreasing percentage of helmet usage while moving towards the locations outside the city was confirmed statistically through t-test (t=1.771, df = 13, p<.05). It was found that only 42% of users revealed that helmets are comfortable and 42% users expressed that helmet affects hearing ability. It is important to note that more than 50% (57%) of users is of the opinion that there is no need to use the helmet if you drive slowly and carefully. The price of the helmet was not a deterrent for helmet use. Also it was observed that only 45% of helmets used by the motorist were standard helmet with ISI (Indian Standards Institute) mark. Conclusion: The widely varying helmet usage pattern observed in the study area may be attributed due to the users’ behaviour that, using a helmet only when the helmet law is strictly enforced rather than using helmet as a protective device. Further, some of the problems and beliefs associated with helmet use prevent the motorcyclists from using helmet. Hence, the road safety of motorcyclists can be improved only through addressing the identified measures comprehensively.